Laws and Ordinances, of a General and Local Nature, for the Government of the City of Cleveland, at 12-13, An Ordinance to Prevent the Firing of Guns, Fire-Arms, or Fire-Works, §§1-2 (1854). - (:unkn) unknown (My University, 1854)
That it shall be unlawful for any person to fire or discharge and cannon, gun, pistol or fire-arms of any kind, within the city,§
Keywords: DISCHARGE